1976
DOI: 10.1128/aem.32.1.68-74.1976
|View full text |Cite
|
Sign up to set email alerts
|

Studies on bacteriophage distribution: virulent and temperate bacteriophage content of mammalian feces

Abstract: Freshly voided samples of the feces of cows, pigs, and humans were analyzed for the enumeration of cell-free plaque-forming units (PFU) of coliphages and Salmonella phages. Coliphage PFU counts per gram (wet weight) of feces were found to range from less than 10' to > 107. Salmonella phages were found in three out of five porcine samples, but none were found in the four bovine samples analyzed. Virulent coliphages related to the OX174/S13 serological group showed some "habitat preference" in that the S13 type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
3

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 14 publications
3
27
0
3
Order By: Relevance
“…It is not even clear where lytic coli phage live under natural conditions. While we have found high densities of lytic coli phage (up to 10 5 per ml) in sewage treatment plants, they are relatively uncommon in feces (Dhillon et al, 1976).…”
Section: Discussionmentioning
confidence: 52%
“…It is not even clear where lytic coli phage live under natural conditions. While we have found high densities of lytic coli phage (up to 10 5 per ml) in sewage treatment plants, they are relatively uncommon in feces (Dhillon et al, 1976).…”
Section: Discussionmentioning
confidence: 52%
“…In the last 20 years, researchers have found that phage are much more numerous in many ecosystems than was traditionally thought and play a more central role in bacterial ecology (Fuhrman 1999;Ashelford et al 2000;Danovaro et al 2001;Breitbart et al 2003;Brabban et al 2005). The presence of phages in the guts of mammals (including ruminants) has been widely described (Dhillon et al 1976;Breitbart et al 2003;Callaway et al 2006;Raya et al 2006). Further, it has been suggested that phage in cattle help maintain microbial diversity and balance, allowing the ecology of the gut, particularly the rumen, to adapt to change (Klieve and Swain 1993;Swain et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is not clear what the expected concentration of E. coli targeting phages is in human fecal samples. Previous studies indicate that plaque forming units (pfu) from human feces on E. coli is in the range of 10 1 -10 7 per gram, with a median concentration of~10 3 per gram 42,43 . Considering that the concentration of E. coli in human feces is in the range of 10 7 -10 9 per gram 44 , interactions between phages and the recording strain might be substantially less common than interactions between commensal E. coli and the recording strain.…”
Section: Discussionmentioning
confidence: 99%